Health-related quality of life of patients and families with primary immunodeficiency in Malaysia: a cross-sectional study - Ahmed Meelad, Ruwaydah; Abd Hamid, Intan Juliana; Zainudeen, Zarina Thasneem; Hashim, Ilie Fadzilah; Azizuddin, Muhd Nur Akmal; Mangantig, Ernest; Taib, Fahisham; Mohamad, Norsarwany; Ismail, Intan Hakimah; Abdul Latiff, Amir Hamzah; Mohd Noh, Lokman (Springer Nature, 2023)
Method This cross-sectional study was performed from August 2020 to November 2020. Patients with PID and their families were invited to answer the PedsQL Malay version (4.0) questionnaire, the tool used to assess the HRQOL. A total of 41 families and 33 patients with PID answered the questionnaire. A comparison was performed with the previously published value of healthy Malaysian children. Result Parents of respondents recorded a lower mean of total score than the parents of healthy children (67.26 ± 16.73 vs. 79.51 ± 11.90, p-value = 0.001, respectively). PID patients reported lower mean total score to healthy children (73.68 ± 16.38 vs. 79.51 ± 11.90, p-value = 0.04), including the psychosocial domain (71.67 ± 16.82 vs. 77.58 ± 12.63, p-value = 0.05) and school functioning (63.94 ± 20.87 vs. 80.00 ± 14.40, p-value = 0.007). No significant difference of reported HRQOL when comparing between subgroup of PID on immunoglobulin replacement therapy and those without immunoglobulin replacement (56.96 ± 23.58 vs. 65.83 ± 23.82, p-value 0.28). Socioeconomic status was found to be predictive of the lower total score of PedsQL in both parent and children reports. Conclusion Parents and children with PID, especially those from middle socioeconomic status, have lower HRQOL and school function impairment than healthy children.